2022
DOI: 10.3389/fnmol.2022.988142
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of retinal membrane guanylate cyclase regulation by GCAP1 and RD3

Abstract: Retinal membrane guanylate cyclases (RetGC1 and RetGC2) are expressed in photoreceptor rod and cone cells, where they promote the onset of visual recovery during phototransduction. The catalytic activity of RetGCs is regulated by their binding to regulatory proteins, guanylate cyclase activating proteins (GCAP1-5) and the retinal degeneration 3 protein (RD3). RetGC1 is activated by its binding to Ca2+-free/Mg2+-bound GCAP1 at low cytosolic Ca2+ levels in light-activated photoreceptors. By contrast, RetGC1 is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…The GCAP5 mutations H18E, M25E and V76E each abolish GCAP5 dimerization and prevent activation of RetGC (Cudia et al 2021 ). These results suggested that GCAP5 dimerization might be essential for RetGC activation (Ames 2021 , 2022 ). However, this hypothesis was refuted by the discovery that the R22A mutation of GCAP5 not only abolishes GCAP5 dimerization but also causes a 300% increase in RetGC activation compared to that of wild type (Cudia et al 2021 ).…”
Section: Biological Contextmentioning
confidence: 93%
“…The GCAP5 mutations H18E, M25E and V76E each abolish GCAP5 dimerization and prevent activation of RetGC (Cudia et al 2021 ). These results suggested that GCAP5 dimerization might be essential for RetGC activation (Ames 2021 , 2022 ). However, this hypothesis was refuted by the discovery that the R22A mutation of GCAP5 not only abolishes GCAP5 dimerization but also causes a 300% increase in RetGC activation compared to that of wild type (Cudia et al 2021 ).…”
Section: Biological Contextmentioning
confidence: 93%
“…And also, NRXN3 is involved in the regulation of tumor proliferation, migration and invasion 25 . The RD3 encodes a retinal protein, which is associated with eye disease 26 . As a protein‐coding gene, SPOCK3 is related to the extracellular matrix organization and integrin pathway.…”
Section: Discussionmentioning
confidence: 99%
“…25 The RD3 encodes a retinal protein, which is associated with eye disease. 26 As a protein-coding gene, SPOCK3 is related to the extracellular matrix organization and integrin pathway. It has been reported that SPOCK3…”
Section: Identification Of the Prognostic Markersmentioning
confidence: 99%
“…A Nuclear Magnetic Resonance (NMR) spectroscopy study indicated that RD3 folds into a three-dimensional structure of a four-helix bundle showing the following arrangement: helix α1: P21-V51; α2: P75-K87; α3: P90-Q107; α4: V111-T139. Point mutations in the central helix α3 of RD3 weaken the RD3 affinity for GC-E [1,7,8]. Genetic deficiencies and mutations of RD3 cause early-onset photoreceptor degeneration in patients with Leber congenital amaurosis type 12 (LCA 12) [4,5,9,10,11].…”
Section: Introductionmentioning
confidence: 99%